Bioaccumulation of copper(II), lead(II) and chromium(VI) by growing Aspergillus niger - Dursun, AY; Uslu, G; Cuci, Y; Aksu, Z (Elsevier Sci Ltd, 2003)
The effect of copper(II), lead(II) and chromium(VI) ions on the growth and bioaccumulation properties of Aspergillus niger was investigated as a function of initial pH and initial metal ion concentration. The optimum pH values for growth and metal ion accumulation were determined as 5.0, 4.5 and 3.5 for copper(II), lead(II) and chromium(VI) ions, respectively. Although all metal ion concentrations caused an inhibition effect on the growth of A. niger, it was capable of removing of copper(II) and lead(11) with a maximum specific uptake capacity of 15.6 and 34.4 mg g(-1) at 100 mg dm(-3) initial copper(II) and lead(II) concentration, respectively. Growth of A. niger was highly effected by chromium(VI) ions and inhibited by 75 mg dm(-3) initial chromium(VI) concentration since some inhibition occurred at lower concentrations. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: bioaccumulation; copper(II); lead(II); chromium(VI); viable Aspergillus niger